A History of Economic Thought: From Aristotle to Arrow - Charles E. Staley (Cambridge: Blackwell, 1994)
This book deals with the major figures in economics, their ideas, their lives, and their influences on subsequent writers and developments of thought. We shall meet people of all kinds - philosophers, theologians, stock-brokers, physicians, mathematicians, and full-time economists - and from many countries. What they had in common was a desire to understand and explain economic phenomena. In the process they contributed to the body of knowledge which exists today and which is ever growing as the presses continue to roll out journals and books on economic theory.
/11426
Keywords: Adam Smith -- Léon Walras -- Alfred Marshall -- David Ricardo